Magnesium batteries : research and applications - Fichtner, Maximilian (RSC energy and environment series, 2020)
The book covers scientific and technical challenges in magnesium battery research, bringing together contributions in the field of anodes, cathodes, electrolytes and systems such as the Mg-S cell.